Studi Eksploratif Terhadap Minat Berkunjung ke Desa Wisata dari Sisi Wisatawan Nusantara - Joanna Vieri Ekamukti; Diena Mutiara Lemy (Tourism Scientific Journal, 2023)
The tourist village is a regional development concept that makes the village a tourist destination. Proper management of all tourist attractions is expected to empower the village community itself. The main principle in a tourist village is a developing village. This principle focuses on improving people's welfare through the development of productive businesses in accordance with local potential and resources. The development of tourist villages is expected to accelerate integrated village development to encourage the welfare of the people in it. Tourism villages that have developed will later have an impact in the form of improving environmental quality, community welfare, and cultural preservation. This research was conducted to explore Tourism Villages from the point of view of tourists, in this case domestic tourists (using a sample of domestic tourists from JABODETABEK). The method used in this study is an exploratory qualitative method, to obtain information from domestic tourists regarding Tourism Villages. The data collection techniques used informal interviews, surveys, and secondary data. Questionnaires were distributed to 150 respondents and also sampling using convenience sampling namely a collection of information from population groups who agree to provide that information.